Faktor Penghambat Pemenuhan Hak Pendidikan Disabilitas di Kota Ambon - Abdin, Maslan; Tetelepta, Johanes Mateos (Jurnal Kewarganegaraan, 2021)
AbstractPeople with disabilities in Ambon City are part of the citizens who must be given the right to education in a fair and non-discriminatory manner by upholding human rights. Obstacle factors in the fulfilment of education will certainly exist. The government as the executor of the constitution is responsible for efforts to resolve it. This study uses a qualitative research design with a case study method. The subjects in this study are schools, parents and the Ambon city government. The results of the identification and analysis found that the factors that hindered the fulfilment of education for persons with disabilities in the city of Ambon, among others (1) parents of students, among others, parents still feel ashamed of the condition of their children, busy parents and access to special schools that are far away. (2) Inadequate school facilities and infrastructure according to the individual needs of each child with disabilities. (3) Only 23% of the accompanying teachers have special education qualifications from the total number of accompanying teachers, namely 116 teachers. On average, the accompanying teachers are classroom teachers and subject teachers with non-special needs education qualifications.-------------AbstrakPenyandang disabilitas di Kota Ambon menjadi bagian dari warga Negara yang harus diberikan hak pendidikannya secara berkeadilan serta tidak diskriminatif dengan menjunjung tinggi hak asasi manusia. Faktor kendala dalam pemenuhan pendidikan pasti akan ada. Pemerintah sebagai pelaksana konstitusi bertanggung jawab dalam upaya penyelesaiannya. Penelitian ini menggunakan desain penelitian kualitatif dengan metode studi kasus, Subjek dalam penelitian ini yaitu sekolah, orang tua dan pemerintah kota ambon. Hasil identifikasi dan analisis menemukan bahwa faktor kendala dalam pemenuhan pendidikan bagi penyandang disabilitas di kota Ambon antara lain (1) orang tua siswa antara lain orang tua masih merasa malu dengan keadaan anak, kesibukan orang tua dan akses ke sekolah luar biasa yang jauh. (2) Sarana dan prasarana sekolah yang kurang memadai sesuai kebutuhan individu masing-masing anak disabilitas. (3) Guru pendamping 23% saja yang berkualifikasi pendidikan khusus dari jumlah keseluruhan guru pendamping yaitu 116 guru. Rata-rata guru pendamping adalah guru kelas dan guru mapel dengan tamatan bukan berkualifikasi pendidikan kebutuhan khusus.